Subdistrict Head Supervision in Efforts to Improve the Performance of Village Officials in Cireunghas District, Sukabumi Regency : Study in Tegalpanjang Village, Cireunghas District - Laela Auleani; Erry Sunarya; R. Deni Muhammad Danial (Dinasti International Journal of Education Management And Social Science, 2024)
This research is entitled Supervision of Subdistrict Heads in Efforts to Improve the Performance of Village Apparatus in Cireunghas District, Sukabumi Regency (Study in Tegalpanjang Village, Cireunghas District). From the author's initial observations, the performance of Village Apparatus has not been optimal, as can be seen from several complaints from several communities regarding public services. Apart from that, the sub-district is also not sensitive to phenomena in the field. The sub-district head, who is legitimized to implement the law, should develop village officials in order to improve their performance in accordance with the law. with its duties and functions. In this research, researchers used a qualitative approach. This research was conducted in Cireunghas District, Sukabumi Regency. Meanwhile, the objects in this research are place, actor and activity. Using combined triangulation and FGD techniques. The informants in this research included: the sub-district head, the sub-district secretary, the village development and supervision section, the head of Tegalpanjang Village, and the general public in Tegalpanjang Village, Cireunghas District, Sukabumi Regency. Data collection through participant observation, structured interviews and unstructured interviews. Study Documentation using tools: Observation Combination, Interview Guide, Field Notes, Data Validation using Triangulation (source, technique and time) and analysis using Reduction, Presenting Data and drawing Conclusions. Village Apparatus Performance (work performance) is the quality and quantity of work results achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. Improving employee performance includes paying attention to supervision from superiors to employees. However, the sub-district head's supervision in an effort to improve the performance of the village apparatus is not yet optimal because motivation and awareness of employee discipline in their work is still lacking, thus becoming an inhibiting factor in the process of sub-district supervision in Cireunghas District, Sukabumi Regency.